2016
DOI: 10.4103/0976-500x.195900
|View full text |Cite
|
Sign up to set email alerts
|

QTc interval in young Gujarati hypertensives: Effect of disease, antihypertensive monotherapy, and coexisting risk factors

Abstract: Objectives:To study the effect of disease duration, treatment and risk factors on QTc interval among young hypertensives.Materials and Methods:A case–control study was conducted on 142 hypertensives (60 males, 82 females) taking calcium channel blocker (CCB) or angiotensin-converting enzyme inhibitor (ACEI) as monotherapy. After blood pressure measurement, we recorded lead II electrocardiograph with minimum ten waveforms. QTc was derived from average of ten values using Bazett's formula. QTc interval >0.43 s i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Higher results in diabetics can also be explained by poor glycemic control despite therapy which is the feature of our diabetics. [12] Such results are in line with a study done elsewhere. [13] It can also be due to (1) unavailability of HbA1c that gives better inference about glycemic control, (2) higher prevalence of physical inactivity, (3) poor blood pressure control, (4) ethnic predisposition, (5) delayed diagnosis, and (6) lack of life style modification.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher results in diabetics can also be explained by poor glycemic control despite therapy which is the feature of our diabetics. [12] Such results are in line with a study done elsewhere. [13] It can also be due to (1) unavailability of HbA1c that gives better inference about glycemic control, (2) higher prevalence of physical inactivity, (3) poor blood pressure control, (4) ethnic predisposition, (5) delayed diagnosis, and (6) lack of life style modification.…”
Section: Discussionsupporting
confidence: 91%
“…We did not find significant difference between new or old cases and with duration less than or more than 4 years with respect to PWA parameters, in line with our previous studies in diabetics with different cardiovascular parameters. [1223242526] It indicates the importance of presence of disease, early diagnosis, physical activity, and prompt treatment more than further chronicity or glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Endless research was nevertheless required to fortify this analysis. 2,[6][7][8] Hence, this study aimed to estimate the prevalence of QTc prolongation among hypertensive individuals and also further evaluate the interrelationship of prolonged QTc with other co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…When these defects exist, they can be easily detected using electrocardiogram (ECG) parameters such as the QT interval. 1,2 Prolonged QT intervals have been linked to an increased risk of cardiovascular death in people with diabetes, hypertrophic cardiomyopathy and heart failure. It has also been linked to several components of insulin resistance syndrome, age, body mass index, left ventricular hypertrophy, persistently elevated blood pressure and, in some studies, female gender.…”
Section: Introductionmentioning
confidence: 99%
“…prone to develop hypertension in India [1]. One of the leading factors for morbidity and It is reported that one in three individuals are mortality worldwide is hypertension [2].…”
Section: Discussionmentioning
confidence: 99%